Adsorption of Monobutyl Phthalate from Aqueous Phase onto Two Macroporous Anion-Exchange Resins. (8th January 2014) - Xu, Zhengwen; Zhao, Yunlong; Shi, Jing; Lu, Jiangang; Cheng, Ling; Chen, Mindong
Abstract : As new emerging pollutants, phthalic acid monoesters (PAMs) pose potential ecological and human health risks. In the present study, adsorption performance of monobutyl phthalate (MBP) onto two macroporous base anion-exchange resins (D-201 and D-301) was discussed. It was found that the adsorption isotherms were best fitted by the Langmuir equation while the adsorption kinetics were well described by pseudo-first-order model. Analyses of sorption isotherms and thermodynamics proved that the adsorption mechanisms for DBP onto D-201 were ion exchange. However, the obtained enthalpy values indicate that the sorption process of MBP onto D-301 is physical adsorption. The equilibrium adsorption capacities and adsorption rates of DBP on two different resins increased with the increasing temperature of the solution. D-301 exhibited a higher adsorption capacity of MBP than D-201. These results proved that D-301, as an effective sorbent, can be used to remove phthalic acid monoesters from aqueous solution.